Using the Syllable Repetition Task to Reveal Underlying Speech Processes in Childhood Apraxia of Speech: A Tutorial. - Rvachew, Susan; Matthews, Tanya (Canadian Journal of Speech-Language Pathology & Audiology)
Purpose: To demonstrate the use of the Syllable Repetition Task (SRT) as a means to identify phonological versus motor planning difficulties in children with suspected Childhood Apraxia of Speech (CAS). Method: Ten children (aged 4.1 - 9.6 years) with suspected CAS were recruited. An extensive assessment battery was administered including measures of speech accuracy, oral motor skills, speech perception and phonological awareness abilities, consistency of word production, and syllable repetition. The SRT yields a memory score (that suggests a phonological planning deficit) and a transcoding score (based on addition errors that suggest a motor planning deficit). Results: Despite overlapping characteristics, especially in the domains of phonological processing, testing revealed three groups: (1) children with deficits in phonological planning, (i.e., low memory scores on the SRT and high word inconsistency); (2) children with deficits in motor planning, (i.e., low transcoding scores on the SRT and prosodic errors); and (3) children with other profiles (i.e., primary deficits in the domain of phonology or language rather than speech production per se). Conclusion: The SRT coupled with a diagnostic measure of phonology and articulation may help to ascertain deficits in underlying speech processes so as to better target intervention procedures to meet the individual needs of these complex children.